ANALISIS PENERIMAAN DANA DESA DAN BELANJA DESA TERHADAP PENGEMBANGAN EKONOMI DI KECAMATAN JEUMPA KABUPATEN BIREUEN - Febrina Febrina; Khairil Anwar; Ratna Ratna (Jurnal Ekonomi Regional Unimal, 2022)
This study aims to analyze the Effect of Village Fund Receipts and Village Expenditures on Economic Development in Jeumpa District, Bireuen Regency. The data used in this study is secondary data in 32 villages. The data analysis method used is multiple linear regression analysis. The results of the study partially received village funds, village expenditures had an effect on economic development in Jeumpa District, Bireuen Regency. Simultaneously, village fund receipts and village expenditures have an effect on economic development in Jeumpa District, Bireuen Regency.